Legal Rights in Access to Health Services for Persons with Disabilities - Subiakso, Andri; Juliarto, Tri Susandhi; Darmawan, Didit; Sisminarnohadi, Sisminarnohadi; Romli, Rido’i Aka (Metromedia, 2023)
In the pursuit of ensuring a satisfactory standard of living for individuals with disabilities, legal protection becomes a crucial necessity, with the right to access health services being one integral aspect. However, the current scenario indicates that health service facilities have not yet attained optimal parity of opportunities between individuals with disabilities and the general public. The objective of this research is to delineate the implementation of legal protection for the right to access health services for individuals with disabilities and to identify potential obstacles that may arise. The research employs a normative legal study approach. The findings reveal that the government has incorporated the right to access health services for individuals with disabilities into statutory regulations, encompassing building requirements and the availability of proficient health personnel to cater to their needs. Nevertheless, obstacles persist in achieving equal access, and this article will delve into a more comprehensive discussion of the challenges and measures necessary to enhance the implementation of legal protection regarding the right to access health services for individuals with disabilities in Indonesia.